Non-invasive quantitative pulmonary V/Q imaging using Fourier decomposition MRI at 1.5T = Erzeugung quantitativer V/Q-Karten der Lunge mit Hilfe von Fourier-Decomposition-MRT bei 1.5T - Kjørstad, Åsmund; Corteville, Dominique; Henzler, Thomas; Schmid-Bindert, Gerald; Zöllner, Frank G.; Schad, Lothar R. (Zeitschrift für medizinische Physik, 2015)
Objectives: Techniques for quantitative pulmonary perfusion and ventilation using the Fourier Decomposition method were recently demonstrated. We combine these two techniques and show that ventilation-perfusion (V/Q) imaging is possible using only a single MR acquisition of less than thirty seconds. Methods: The Fourier Decomposition method is used in combination with two quantification techniques, which extract baselines from within the images themselves and thus allows quantification. For the perfusion, a region assumed to consist of 100% blood is utilized, while for the ventilation the zero-frequency component is used. V/Q-imaging is then done by dividing the quantified ventilation map with the quantified perfusion map. The techniques were used on ten healthy volunteers and fifteen patients diagnosed with lung cancer. Results: A mean V/Q-ratio of 1.15±0.22 was found for the healthy volunteers and a mean V/Q-ratio of 1.93±0.83 for the non-afflicted lung in the patients. Mean V/Q-ratio in the afflicted (tumor-bearing) lung was found to be 1.61±1.06. Functional defects were clearly visible in many of the patient images, but 5 of 15 patient images had to be excluded due to artifacts or low SNR, indicating a lack of robustness. Conclusion: Non-invasive, quantitative V/Q-imaging is possible using Fourier Decomposition MRI. The method requires only a single acquisition of less than 30 seconds, but robustness in patients remains an issue.
Gesehen am 24.05.2017